Drug-induced liver injury associated with dacomitinib: A case report - Wang, Xuanxuan; Huang, Anqi; Lu, Yun; Gao, Suyu; Hu, Wen; Cheng, Hong (Frontiers in Oncology, 2022)
Dacomitinib, the second-generation epidermal growth factor receptor tyrosine kinase inhibitor (EGFR-TKI), has been used as first-line treatment in non-small-cell lung cancer (NSCLC) patients harboring EGFR mutation. In this case, we report a patient of drug-induced liver injury (DILI) associated with the use of dacomitinib. A 59-year-old man with stage IV NSCLC was prescribed dacomitinib, 37 days after dacomitinib administration, he was admitted to our hospital because of jaundice. Laboratory examinations revealed elevated serum levels of liver enzymes and bilirubin. Following the immediate discontinuation of dacomitinib, liver enzymes decreased but bilirubin continued to rise. Total bilirubin reached the peak (18-fold) on day 26 after dacomitinib termination, and normalized on day 146 after dacomitinib discontinuation. A ‘probable’ cause of DILI by dacomitinib was determined based on the Roussel Uclaf Causality Assessment Method. The severity of DILI was assessed as acute liver failure. To our knowledge, this is the first case of DILI caused by dacomitinib monotherapy in a real-world setting. Clinicians should pay particular attention to the possibility of DILI during dacomitinib treatment.